Museums "at the heart of community": local museums in the post-socialist period in Slovenia - Hudales,Joe (2007)
The author tries to define the changing role of local or community museums in the last few decades, when the crisis of museum institutions became a fact and when museum institutions were very often labeled as "fossilised", "ossified" and conservative institutions, and that are now facing the ongoing fast social changes. He points out that Slovenian museums, in the last decade of socialist and post-socalist rule, have also gone through the same development. The first "incentives" for making necessary changes in museums and for using different methods and approaches came after 1980, mostly in local and regional museums, and most of the new approaches and efforts for transformation came from ethnologists. Finally, he describes his personal museum experience in three museum projects from 1993, 2000 and 2006 where he tries to "humanize" museum objects and solve some problems concerning "museum crisis".